Towards the measurement of enterprise information systems agility to support EIS improving projects. (2018) - Laval, Jannik; Cherifi, Chantal; Cheutet, Vincent
Enterprise information systems (EIS) are directly implied in the global performance of an organisation. Nevertheless, their potential rigidity in comparison with the required fast evolution of the supported organisation remains an important open research question. The proposed research work aims to define and evaluate the agility of an EIS, in order to assist both software engineers and business managers in EIS improvement projects. In particular, a framework is proposed to structure the different existing metrics on agility according to the improvements needs and the intrinsic characteristics of an information system.